2015
DOI: 10.1002/stc.1777
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of wood structural members degradation by means of infrared spectroscopy: an overview

Abstract: Timber structures can undergo alteration during their service life, which can be caused by mechanical, environmental or biological agents (bacteria, fungi and insects), because of the biological nature of the material. On site characterization of timber members is a very challenging task, especially assuming that both, the structure itself and material used for construction have to be evaluated. Current assessment procedures are limited to visual inspection, occasionally supported by a few instrumental analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 56 publications
(62 reference statements)
0
25
0
Order By: Relevance
“…The issue of collecting representative spectra again exists, but results are promising and owing to its ability to estimate a range of properties simultaneously [33] NIR could have an important role in sawmills in the future. In related research, the assessment of MOE and load for wood in service has recently been demonstrated [35][36][37].…”
Section: Journal Of Spectroscopymentioning
confidence: 99%
“…The issue of collecting representative spectra again exists, but results are promising and owing to its ability to estimate a range of properties simultaneously [33] NIR could have an important role in sawmills in the future. In related research, the assessment of MOE and load for wood in service has recently been demonstrated [35][36][37].…”
Section: Journal Of Spectroscopymentioning
confidence: 99%
“…Wood subjected to weathering is degraded by various environmental agents such as solar radiation, cyclic wetting, atmospheric temperature and relative humidity changes, environmental pollutants and certain micro-organisms. The characteristic grey patina visible after few months of exposures is mostly caused by photodegradation of lignin in middle lamella by UV radiation 1 Near infrared spectroscopy and hyperspectral imaging are perfect scientific tools for rapid and non-destructive characterization of wood surfaces 2,3,4 . The great advantage of both techniques is the possibility of determining both chemical and physical properties of a large number of samples.…”
Section: Introductionmentioning
confidence: 99%
“…Two main processes are assumed to take place under the conditions of the accelerated weathering test. According to the literature changes in the resin content due to temperature and photodegradation of lignin due to UV radiation could be expected [9][10][11][12]. PCA were, therefore, based on the wavenumber range 1930-400 cm − 1 where relevant bands contribute to sample segregation ( Table 2).…”
Section: Effect Of Accelerated Weatheringmentioning
confidence: 99%